Controlled copolymerization of n-butyl acrylate with semifluorinated acrylates by RAFT polymerization. Issue 3 (14th October 2014) - Chen, Senbin; Binder, Wolfgang H.
Abstract : A new class of well-controlled semifluorinated copolymers were successfully synthesized via RAFT polymerization. We found that ESI-TOF MS was particularly useful for readily analysing our semifluorinated copolymers. The reactivity ratios of each pair of co-monomers are close to one. Abstract : By reversible addition fragmentation chain transfer (RAFT) copolymerization of n -butyl acrylate ( n BuA) with semifluorinated acrylates, such as 2, 2, 2-trifluoroethyl acrylate (TFEA), 2, 2, 3, 3, 3-pentafluoropropyl acrylate (PFPA) and 2, 2, 3, 3, 4, 4, 4-heptafluorobutyl acrylate (HFBA), up to 90.2% co-monomer conversion was accomplished. When using dibenzyl trithiocarbonate (DBTTC) as a chain transfer agent (CTA) in DMF at 65 °C, excellent control of molecular weight ( M n ) together with a low molecular weight distribution (PDI) was achieved. The successful synthesis of well-controlled semifluorinated copolymers was checked by a combination of 1 H NMR, 19 F NMR, SEC and ESI-TOF mass spectrometry, proving their composition via 1 H NMR and ESI-TOF mass spectrometry. The reactivity ratios ( r ) of each pair of co-monomers were assessed using Fineman–Ross (FR) and Kelen–Tüdos (KT) laws: in all cases, the product ( r M1 × r M2 ) was close to unity, indicating a random distribution of each pair of co-monomers along the semifluorinated copolymer backbone. Results were further confirmed by applying the Q – e scheme.